2016
DOI: 10.1097/meg.0000000000000538
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the ability of the PDD-ICG clearance test, CTP, MELD, and MELD-Na to predict short-term and medium-term mortality in patients with decompensated hepatitis B cirrhosis

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 21 publications
(22 reference statements)
3
14
1
Order By: Relevance
“…Decompensated cirrhosis is a common disease with high morbidity and may be accompanied by several manifestations of decompensation, including gastrointestinal hemorrhage, hepatic encephalopathy, and infection. Consistent with a previous study on patients with liver cirrhosis, approximately 11.0% of patients with decompensated cirrhosis died within 28 days and 20% died within 6 months in the present study [26][27][28]. To reduce mortality, it is crucial to recognize those patients with a potentially poor prognosis and then prioritize and treat them accordingly in an appropriate and timely manner.…”
Section: Discussionsupporting
confidence: 87%
“…Decompensated cirrhosis is a common disease with high morbidity and may be accompanied by several manifestations of decompensation, including gastrointestinal hemorrhage, hepatic encephalopathy, and infection. Consistent with a previous study on patients with liver cirrhosis, approximately 11.0% of patients with decompensated cirrhosis died within 28 days and 20% died within 6 months in the present study [26][27][28]. To reduce mortality, it is crucial to recognize those patients with a potentially poor prognosis and then prioritize and treat them accordingly in an appropriate and timely manner.…”
Section: Discussionsupporting
confidence: 87%
“…The MELD score has a predictive value for both in-hospital mortality and bacterial infection incidence in patients with cirrhosis [46]. The CTP score is also known to have predictive significance in short-term and medium-term mortality evaluations in patients with liver cirrhosis [47]. The present study shows that both the CTP and MELD scores may also discriminate patients with a lower and higher risk of infection; however, the odds ratio and AUC for CTP and MELD scores are lower than those for the LMR.…”
Section: Discussionmentioning
confidence: 99%
“…[11] AUC of MELD-Na of this study was found to be 0.70, which was relatively lower than that of other studies, of 0.85 to 0.92. [13,16,17] However, according the suggestion of Muller et al, [23] its diagnostic performance ranged from good-excellent. It would be attributable to its significantly longer follow-up period, of 14 years, than other studies of which follow-up periods were up to 20 months, and the relatively lower AUC of this study might be because it included data from even cases censored during the follow-up period in order to reduce bias in its results.…”
Section: Discussionmentioning
confidence: 99%
“…[12,13] Studies on the prognosis of patients with cirrhosis have been mostly focused on terminal cases and anticipation of short-term mortality, and most of them highlight the analysis of prognosis of patients with cirrhosis rather than classification of patients considering the level of severity. [14][15][16][17][18][19] Moreover, the analysis of prognostic factors for mortality of patients should include not only disease-related factors, but also personal and social factors. Such analysis could provide a comprehensive and systematic understanding of patients diagnosed with cirrhotic complications.…”
Section: Introductionmentioning
confidence: 99%